Observation of plasma bubble ionospheric equatorial at peninsular Malaysia by using myRTKnet / Noor Hijjah Mohamad Yusof - Mohamad Yusof, Noor Hijjah (2011)
This thesis presents the research on observation of plasma bubble ionospheric equatorial at peninsular Malaysia by using Malaysian Real Time Kinematic Global Positioning System Network (myRTKnet). Depletion layer in Total Electron Content (TEC) in ionospheric layer is called plasma bubbles which usually occur during midnight. The research on observation of equatorial plasma bubbles (EPBs) ionospheric at peninsular Malaysia by using Malaysian Real Time Kinematic Global Positioning System Network (MyRTKnet) can be observed by ionosonde, radar, satellite, Global Positioning System (GPS)-receiver and being measured by using MyRTKnet. In this project, we will focus on data taken by GPS receiver only. This determination is made for satellites in Peninsular Malaysia in the September period of 2007. But only satellites at Universiti Utara Malaysia (UUMK) and Sungai Petani (SGPT) will be considered in this research. The important parameter in this project is TEC which is the value of TEC change rate; ATEC is taken within the period of every 15 seconds in order to detect Plasma Bubble. TEC is extracted using GPS receiver which in PJNEX format that supplied by JUPEM (Department Of Survey and Mapping Malaysia) and taken from receiver station located at UUMK and SGPT. The value of ATEC is compared base on the dropness of TEC value within the scale. It is shown that most equatorial plasma-bubble events commence at 18:00 UT on 6th September 2007 for PRN 26, and may last for less than 60 min.